Legal issues of human shields - Zaļā, Laura (Riga Graduate School of Law, 2022)
The paper focuses on analyzing whether the civilians involved in the hostilities as involuntary human shields enjoy the same legal protection under the law as voluntary human shields. The author looks at the differences between voluntary and involuntary human shields and the aspect of direct and indirect participation in hostilities. The analysis is based upon International Law and Criminal Law articles and interpretations concerning the notion of human shields. In addition, multiple cases where the human shields were observed, were also examined to understand the court practice on how the court deals with the law breaches in contemporary armed conflicts.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Research Subject Categories::LAW/JURISPRUDENCE::Criminal law; Voluntary human shields; Involuntary human shields